Factor contribute to SOCSO’S service quality: a study on Tesco Bandar Melaka employee / Mohd Hilmi Mohd Nasir - Mohd Nasir, Mohd Hilmi (Faculty of Business and Management, 2011)
Service quality can be defined as focusing on meeting customers’ needs and requirements and how well the service delivered meets their expectations. The Social Security Organization (SOCSO) was established on the 1st of January 1971 as Government Department to enforce the Employee’s Social Security Act, 1969. On the 1st of July 1985, SOCSO became a Statutory Body. Total people that contribute to SOCSO is enormously in large amount Industrial accidents claims registered by the Social Security Organization (SOCSO) increased by 19.1 per cent to RM1.549 billion last year, said Deputy Human Resources Minister Datuk Maznah Mazlan. Recently SOCSO had launched Socso's Saturday services which the counters are open on Saturday and it gets positive impact on their customer. The services will initially be available at the Jalan Ampang Socso headquarters and Socso offices in Jalan Tun Razak, Kuala Lumpur and Jalan Selangor here.(New Straits Times, 2011 January 9) Based on the above, there is evidence to the existence of high demand of service in SOCSO. The purpose of this study is to determine what factor that contributes to service quality on SOCSO and the most influence factor that contributes to SOCSO’s service quality